A Class III look with Buccally placed high Canine of an Angle's Class I Malocclusion treated in a Non Extraction approach (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Class I malocclusion also called neutro-occlusion, this describes a normal molar relationship but there is malposition of one or more individual teeth. Treatment of Class I malocclusion varies depending on the condition and severity. However, the purpose of this report is to review the orthodontic treatment of a Class I malocclusion with buccally placed canine without extraction. This case report describes a 13-year-old girl with a Class I malocclusion, anterior and posterior crossbite, a retrusive maxilla with high canine. The Class I malocclusion with posterior crossbite was corrected with quad helix followed by non extraction orthodontic treatment with fixed appliances to correct anterior crossbite. At the end of treatment we obtained an acceptable occlusion relationship and the facial profile and the patient's smile were improved substantially.Ban J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P.20-22